Low-dose post-transplant cyclophosphamide with G-CSF/ATG based haploidentical protocol provides favorable outcomes for SAA patients - Ma, Xiaodi; Xu, Zhengli; Han, Tingting; Zhang, Yuanyuan; Han, Wei; Fu, Haixia; Zhang, Xiaohui; Lin, Fan; Huang, Xiaojun; Xu, Lanping (Frontiers in Immunology, 2023)
Haploidentical hematopoietic stem cell transplantation (haplo-HSCT), as one of the life-saving treatments for severe aplastic anemia (SAA), is widely used because of its great donor availability. Over decades, granulocyte colony-stimulating factor (G-CSF)/ antithymocyte globulin (ATG)-based protocol (the so-called Beijing Protocol) has achieved favorable engraftment and survival outcomes. In this study, we modified the conventional Beijing Protocol: the full-dose Cyclophosphamide (Cy) (200 mg/kg in total) was divided into 42.75 mg/kg Cy on day -5 to day -2 and Low dose post-transplant Cy (PTCy) (14.5 mg/kg on days +3 and +4), hoping to reduce the incidence of severe acute graft-versus-host disease (aGVHD) and to guarantee successful and stable engraftment. Here we retrospectively reported and analyzed the data of first 17 patients with SAA who had received haplo-HSCT using this novel regimen between August 2020 and August 2022. The median follow-up was 522 days (range, 138-859 days). No patient developed primary graft failure. Four (23.5%) patients developed grade Ⅱ bladder toxicity, two (11.8%) patients developed grade Ⅱ cardiotoxicity. All patients achieved neutrophil and platelet engraftment at median times of 12 days (range, 11–20 days) and14 days (range, 8-36 days). During our follow-up, no patients developed grade Ⅲ-Ⅳ aGVHD. The cumulative incidence of grade Ⅱ and grade Ⅰ aGVHD at 100 days was 23.5% (95% CI, 1.0%-46.0%) and 47.1% (95% CI, 20.6%-73.5%). Three four patients (17.623.5%) developed chronic GVHD of skin, mouth, and eyes and all of which were mild. All patients are alive by the end of the follow-up, with a failure-free survival of 100%, which was defined as survival without treatment failures, such as death, graft failure, or relapse rate. The rate of cytomegalovirus (CMV) reactivation was 82.4% (95% CI, 64.3%-100%). The rate of Epstein-Barr virus (EBV) reactivation was 16.7% (95% CI, 0%-35.7%). No CMV disease and post-transplantation lymphoproliferative disorder (PTLD) occurred among these patients. In conclusion, the encouraging results of prolonged survival outcomes and reduced incidence of GVHD suggest promising effect of this novel regimen in haplo-HSCT for patients with SAA. Larger-sample prospective clinical trials are needed to confirm the effectiveness of this regimen.